Economy, Business and Uncertainty: New Ideas for a Euro-Mediterranean Industrial Policy - Gil-Lafuente, Jaime; Marino, Domenico; Morabito, Francesco Carlo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents original research articles addressing various aspects of economics, management and optimization. The topics discussed include economics, finance, marketing, resource allocation strategies, fuzzy logic, and network-based techniques for the analysis of economics, management and mathematical optimization. Combining the input of contributing professors and researchers from various Spanish, Italian and Latin American universities, the book will be of interest to students, researchers and practitioners, as well as members of the general public interested in the world of Economics and Management.
Introduction -- Bibliometric Analysis on Customer Dissatisfaction -- Holistic Learning Evidences in the Supervised Teaching Practice Reports -- Assessing Overall Fit and Invariance in a PLS Model -- Collective Well-Being with a Synthetic and Autocorrelate index Tourism -- Cooperation for External Knowledge Acquisition from Inter-Organizational Relationships as Antecedent of Product Innovation -- Recent trends in volunteerism -- Effect of the Spanish sovereign risk premium on the IBEX 35 -- The revolution of active methodologies -- Value Investment using stock index -- Board resources and firm performance in SMEs -- An evaluation of territorial gaps in Italian Health -- Introduction of Experiential Learning, use of ICT and influence on academic results and performance -- The dimensions of service quality -- Relationship between innovation process and innovation results -- E-commerce decision-making factors in Peruvian organizations of the retail sector -- Emotional legitimacy -- Hierarchization offactors involved in the failure of startups -- Public's behaviour in front of sports -- The LWP and TES: assessment and evaluation -- Using method of expertons in bidder selection on the spanish public procurement process -- The Approach of the Entrepreneur Microecosystem for University Entrepreneurial Education -- Does the Performance of the Company Improve with the Digitalization and the Innovation? -- Strategic Functions Manufacturer-Distributor in Marketing Channels -- The Italian approach to Industry 4.0 -- Theoretical aspects on the indicence of port dynamics in the local economy -- Theoretical Aspects of the Creation of Value for the Client -- Consequences of poor accounting practices -- The Gender Gap of Retirement Pensions in Spain, Causes and Improvements in the Legal Order.
Keywords: Computational intelligence; Econometrics; Industrial Management; Europe -- Economic conditions; Computational Intelligence; Quantitative Economics; Industrial Management; European Economics